Increase in the Deposition of Aggregated Protein in the Glomeruli of Spontaneously Diabetic Mice - Tadashi Nagamatsu; Yasushi Hirasawa; Shoko Ohtsu; Kazusuke Yamane; Tohru Toyoshi; Kohei Kyuki; Yoshio Suzuki (Elsevier, 2005)
The aim of this study was to investigate the disposal of aggregated protein in the glomeruli of spontaneously diabetic mice. Diabetic mice, KK-Ay and db/db, and age-matched ICR mice were injected intravenously with aggregated bovine serum albumin (a-BSA) at 0.6 mg/g, and the glomeruli and the blood were obtained. Diabetic mice had larger amounts of a-BSA in their glomeruli than the ICR mice, threefold in KK-Ay and twofold in db/db, at 3 h after the a-BSA injection. Additionally, the disappearance of a-BSA was retarded in the diabetic glomeruli. KK-Ay displayed a-BSA in the glomeruli 24 h after the a-BSA injection and db/db did after 12 h, while the ICR did by 8 h. In spite of increases of insulin to similar degrees in both strains of diabetic mice after the a-BSA injection, blood glucose levels markedly decreased in KK-Ay compared with db/db. There were no histopathological alterations in the glomeruli of the diabetic mice. Depositions of a-BSA were confirmed to be higher in the diabetic glomeruli by the immunofluoresnce technique, and KK-Ay displayed higher depositions of a-BSA than did db/db. The present study suggests that hyperglycemia is involved in the increased deposition of aggregated protein in the glomeruli and that the degradation of aggregated protein is retarded in diabetic glomeruli. Keywords:: diabetic mice, diabetic nephropathy, glomeruli, aggregated protein, hyperglycemia